PENGETAHUAN, RASA TAKUT DAN DUKUNGAN ISTRI TERHADAP MINAT PRIA DALAM KB VASEKTOMI DI PUSKESMAS TILANGO - Harismayanti Harismayanti; Ani Retni (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
This study aims to determine the relationship to men's interest in using Contraceptive of Male Operative Medical. The design of this study used an observational research with cross-sectional approach. Sampling was done by simple random sampling technique, sample numbered 97 people. Data analysis was performed univariate and bivariate with chi-square test. The results showed that there was a significant correlation between knowledge (p = 0,01), fear (p 0,00), wife support (p = 0,00) influencing to men interest in using Male Operative Medical contraception tool. The researcher suggests that it can be used as input data about contraceptive of Male Operative Medical to further improve in providing new information, counseling and Services about male contraceptive to the community so that it can provide optimal benefits by minimizing side effects or complaints.